Study of the yeast cytosolic Hsp70-system in protein homeostasis and life span regulation - Immunocytofluoroscense of Hsp70-mutant yeast strains with primary antibodies against Hsp42p - Vielfort, Katarina; Andersson, Rebecca; Nyström, Thomas (University of Gothenburg, 2020)
Our study aims to answer the question "Which functions of the Hsp70 class of molecular chaperones are essential for yeast to maintain a standard replicative life span?". To answer this question, we utilised the disparate functions of the Hsp70's Ssa1 and 2 and their paralog Ssa4 in a yeast strain that lacks Ssa1/2 but has an ectopically increased production of Ssa4. We have gathered data on the behaviour of several different markers for protein aggregation under different circumstances, as well as data on proteins from other classes of molecular chaperones. The bulk of the data is in the form of multichannel microscopy images from widefield microscopy, with a few sets of western blots of protein extracts.

Fluorescence microscopy of fixated yeast cells at mid-exponential growth. The samples have been stained with antibodies against Hsp42 (primary antibody: rabbit anti Hsp42, secondary antibody: goat anti rabbit Alexa Flour488) and counterstained with DAPI (datasets from 170505 and 170608) and antibodies against Actin (primary antibody: mouse anti- Act1, secondary antibody: goat anti mouse Alexa Flour 568) (dataset from 170518) or nucleoporin complexes (dataset from 170608) (primary antibody: mouse anti- Nsp1, secondary antibody: goat anti mouse Alexa Flour 568).
The dataset was collected through fluorescence microscopy.
The image files are provided in Carl Zeiss Image format (.czi).

Vi har systematiskt studerat vilka funktioner hos de cytosoliska molekylära chaperonerna av klassen Hsp70 hos jäst som krävs för att upprätthålla en normal livslängd.

Immunocytofluorescensbilder av jästceller som fixerats i mitten av den exponentiella tillväxtfasen. Cellerna har färgats med antikroppar mot Hsp42 (primär antikropp: kanin anti-Hsp42, sekundär antikropp: get anti-kanin AlexaFlour488) och kontrastfärgats med DAPI (dataset från 170505 och 170608), antikroppar mot aktin (dataset från 170518) (primär antikropp: mus anti-Act1, sekundär antikropp: get anti-mus Alexa Flour568) eller nukleoporinkomplexet (dataset från 170608) (primär antikropp: mus anti-Nsp1, sekundär antikropp: get anti-mus Alexa Flour568).
Datasetet har hämtats in med fluorescensmikroskopi.
Bildfilerna är i Carl Zeiss Image-format (.czi).
Studier av det cytosoliska Hsp70-systemet från jäst och dess roll i proteinhomeostas och reglering av livslängd - Immunocytofluorescens av Hsp70-mutanta jäststammar med primära antikroppar mot Hsp42p
Keywords: Molecular Chaperones; Molekylära chaperoner; HSP70 Heat-Shock Proteins; HSP70-värmechockproteiner; Proteostasis Deficiencies; Proteostasbrist; Cell Biology; Cellbiologi; Microbiology; Mikrobiologi; Cell and Molecular Biology; Cell- och molekylärbiologi; Molecular Biology; Molekylärbiologi